(untitled) (Ciudades, 2017)
The Asturian midlands, with vague limits but gathering three quarters of the population in the region on one quarter of the territory, is a clear example of the various difficulties coming up from diffused conurbation. Lacking a definitive theoretical description and, above all, being conscious of the complexities to administrate the functional metropolitan area, such matters will be tackled hereafter and some technical and regulatory attempts to solve the present-day problems will be summarized as well. Distinctive for its polycentric configuration from its origins, the overlay of the Anglo-Saxon urban model on heterogenic municipalities ended up by making administration difficult in a field short of a whole territory planning which cannot linger on unattended any longer.